The Influence of Facilities and Infrastructure on Learning Effectiveness at Insan Prima Bekasi National School - Christianus Gumilar Akoso; Daniel S. Tjandra (Manajia: Journal of Education and Management, 2025)
The school facilities can affect the effectiveness of learning process. The existence of school facilities such as libraries and computer laboratories provide opportunities for students to read references outside the student handbook. Classrooms that are not crowded allow students to carry out various learning activities. The functioning of facilities and infrastructure also affects students in following the learning process well. Classrooms that are hot or cold provide discomfort for students in participating in learning.  This research aims to provide evidence that the existence and functioning of school facilities and infrastructure can have a positive influence on students in participating in the learning process. By using qualitative methods in the form of interviews and direct observation, the data was analyzed to see the influence of facilities and infrastructure in learning process. The conclusion of this research shows that the existence of facilities and infrastructure owned by the school helps students to follow learning process well. Teachers can apply more diverse learning methods and strategies. The non-functioning of facilities and infrastructure provides inconvenience and inhibits students from participating in learning process well. In addition to that, teachers have limitations in applying learning methods and strategies in the learning process.